Análisis de la retención y secuestro de mercancías como medida preventiva por infracciones aduaneras estipulada en el Código Orgánico de la Producción, Comercio e Inversiones “COPCI - Martínez Mendoza, Adriana Salome (2023)
The present thesis entitled "Analysis of the Retention and Seizure of Goods as a Preventive Measure for Customs Violations stipulated in the Organic Code of Production, Commerce and Investment "COPCI", and its interest to develop is in view of analyzing whether the application of this preventive measure is effective in limiting or reducing the commission of customs offenses in our country, since these greatly affect economic development and it has been shown that they contribute to the occurrence of cases of corruption. The study shows that this measure is not entirely effective, the poor performance of officials has a little impact on its ineffectiveness, being that some of the officials are not trained to perform effective control of goods entering or leaving the country, likewise controls are not performed at certain times to curb the commission of customs offenses, the following research allowed to identify whether the institution in the city of Catamayo has the necessary infrastructure to carry out the provisional retention of goods, In addition to propose a mechanism for improvement to prevent consignees from committing customs violations, in the same way it was possible to establish what are the possible weaknesses and strengths in terms of its administration, to ensure that there is an effective compliance with the rule in case it were to be broken, with the sanctions stipulated in the Organic Code of Production, Trade and Investment. Within this investigation, materials and methods were applied which allowed the development of the investigation, as well as interviews and surveys to legal professionals, whose results allowed the development of the conclusions and recommendations of the investigation, in order to correctly apply the collection of fines for customs violations and the effective operation by customs agents, to ensure the principle of proportionality in addition to the procedural speed, trying to eliminate these acts with sanctions or penalties.